Granny Smith Was Not An Apple : the story of orchardist Marie Ann Smith - Fortson, Sarah Glenn; McLeod, Kris Aro (Rye Brook, New York : Peter Pauper Press, Inc., 2023)
"In the 1800s a migrant farmer named Maria Ann Smith worked as an apple orchardist. Her discovery of a new type of apple that never turned red, but was always green, tart, sweet, and perfect for a pie, was due part to a fluke of nature, and part to Maria's insight and determination. The beloved Granny Smith apple that we know today was named in her honor. This is her story"--.
new kids book 2023 fall.
Includes bibliographical references.
Ages 4-8
Grades K-1
Keywords: Smith, -- Granny, -- 1799-1870 -- Juvenile literature; Apple growers -- Australia -- Ryde (N S W ) -- Biography -- Juvenile literature; Apples -- Juvenile literature -- Growth; Apples -- Varieties -- Juvenile literature